The Pattern of Acute Abdomen in Sulaimany Teaching Hospital - Faraj, Faruk H. (Sulaimani Journal for Pure and Applied Sciences, 2000)
A total of 520 patients entered this study. The most common cause of acute abdomen was acute appendicitis (33.46%) followed by urological causes (27.88%), non-specific abdominal pain (NSAP) (1 1.34%) and hiliary diseases (8.84%). Male female ratio was 48:52 in the whole study population , but there were differences in the age and sex distribution when studied by diagnosis. Acute appendicitis was more frequently found in young men , NS AP was mainly presented in young women and hiliary disease was most common in adult and elderly women. A male predominance was noted in cases of renal stones, and peptic ulcer. 47.6 % of patients were operated on and surgery was most common for patients at 2"d-3'd decades of life for appendectomy and at 4th-6m decades of life for D. U and hiliary surgery. Altogether 5% ofpatients were discharged without hospitalization. Six patients (1.1%) died of various causes , the most common of which was intestinal obstruction(3 patients).